A General Bibliometric and Conceptual Structure Approach to Global Trend on Poverty Research in Islam Using Biblioshiny - Mustafar, Mohd Zaid; Ruslan, Ashraff; Mohd Aziz, Mohd Khairul Nizam; Sharif , Dziauddin; Lokman , Md Azzaat Ahsanie; Mat Roni, Saiyidi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
This study maps the intellectual landscape of research on poverty in Islam using a structured bibliometric approach with Biblioshiny (Bibliometrix) in RStudio. A Scopus search (TITLE-ABS-KEY “poverty” AND “Islam”) conducted on 1 September 2023 identified 279 English-language journal articles published between 1976 and 2023. The corpus spans 227 sources, 646 authors, and 10,262 cited references, with an annual growth rate of about 5%. Performance and science-mapping analyses reveal two “motor themes”—Islamic finance and healthcare/public health—while spiritually anchored constructs (e.g., maqasid, zakat governance, waqf, spiritual poverty) remain peripheral in co-occurrence and thematic maps. Citation patterns indicate higher field-normalized impact when studies are placed in multidisciplinary outlets, suggesting scope to bridge Islamic social-finance debates with mainstream development and health discourses. Methodological limitations include reliance on a single database (Scopus) and a narrow query that may under-capture related terms (e.g., “zakat”, “waqf”), which should be expanded in future replications. Overall, the review identifies key authors, venues, and conceptual clusters; highlights blind spots in spiritually grounded frameworks; and offers a roadmap for aligning Islamic social-finance instruments with maqasid-oriented outcomes in poverty alleviation.